Kazimierz Marcinkiewicz jako publicysta miesięcznika katolickiego "Aspektv". Wizja państwa i społeczeństwa polskiego w pierwszych latach III RP = Kazimierz Marcinkiewicz as a publicist for the monthly catholic magazine "Aspekty". The view of the Polish country and community in the first years of the third republic of Poland - Bielska, Anna Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Kazimierz Marcinkiewicz was connected to the catholic magazine "Aspekty" in the years1985-1996. He was one of the magazine's editors and an author of many articles published in"Aspekty". His articles concern some chosen issues of sociopolitical life. The prevailing subjectswere related to family, its function in the life of the nation, the matter of raising youngergenerations according to Christian values or the meaning the Catholic church has in Poland andthe religious life of Poles.
Keywords: Marcinkiewicz, Kazimierz (1959- ); publicystyka polska; czasopismo katolickie